MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MELALUI PUZZLE TETRIS PADA ANAK KELOMPOK B DI TK PUSAT PAUD TUNAS INTI BATURAPPE KECAMATAN BIRINGBULU KABUPATEN GOWA - Lidia; Nur Alim Amri; M. Yusran Rahmat (STKIP Subang, 2023)
The main problem in this study is how to improve the cognitive ability of learning and problem solving of children. The purpose of this study is to improve the cognitive ability of learning and problem solving in children through tetris puzzle games. The type of research used is class action research consisting of planning, implementation, observation and reflection. His research subjects were 19 students. The results of this study showed that in cycle I of 19 children, improvement in learning and problem solving through tetris puzzles, in cycle I achieved an average score of 47.7% with the category starting to develop (MB). While in cycle II of 19 children, an average score of 78.2% was obtained with excellent development criteria (BSB). Based on the results of the study, it can be concluded that the cognitive ability of learning and problem solving children through tetris puzzle games in group B at the Central Tk of Paud Tunas Inti Baturappe, Biringfuru District, Gowa Regency has improved.